(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses the factors that contribute to the development of students of general education schools today in the field of fine arts, which are intellectually, spiritually, ecologically educated, intensively thinking and proactive, and the thoughts of great thinkers.